Characteristics of Disorder‐Related Autobiographical Memory in Acute Anorexia Nervosa Patients. (20th June 2015) - Huber, Julia; Salatsch, Carmen; Ingenerf, Katrin; Schmid, Carolin; Maatouk, Imad; Weisbrod, Matthias; Herzog, Wolfgang; Friederich, Hans‐Christoph; Nikendei, Christoph
Abstract Objective First studies revealed overgeneral autobiographical memories in anorexia nervosa (AN) patients. The aim of the present study was to investigate frequency, generalization and valence of autobiographical memories in AN patients in response to eating disorder‐related cue words. Method Autobiographical memory was examined in 21 AN patients and 21 healthy controls (HC) using a modified version of the Autobiographical Memory Test, incorporating body‐related, food‐related, perfectionism‐related, depression‐related and neutral cues. Results Anorexia nervosa patients recalled fewer and more general autobiographical memories compared with HC. For eating disorder‐related cues as against neutral ones, AN patients compared with HC showed fewer memories for food‐related and body‐related cues, an elevated overgeneralization for food‐related cues, while the valence of the retrieved memories was more negative in response to body‐related cues. Discussion This study detects disorder‐related autobiographical memory alterations in AN, which are intensified in response to symptom‐related cues. The findings are discussed with regard to their maladaptive function in emotion regulation. Copyright © 2015 John Wiley & Sons, Ltd and Eating Disorders Association.